Physical Activity Solutions to Decrease Occupational Stress. (May 2023) - Aslakson, Aaron; Melton, Bridget; Bland, Helen; Biber, Duke
Abstract : Occupational stress impacts employees, organizations, and potential customers. Physical activity as a coping mechanism can help to mitigate the adverse outcomes of occupational stress. Physical activity solutions for employees allow employees to initiate and maintain a physically active lifestyle, potentially mitigating the adverse outcomes of occupational stress. Apply It!: After reading this article, fitness professionals will be able to: Understand the impact of occupational stress on employees. Understand how physical activity impacts occupational stress. Implement suggestions for on-site physical activity solutions and off-site physical activity promotion to impact occupational stress.